The Effect of Participation in Budgeting, Utilization of Information Technology, and Budget Revision on the Effectiveness of Surabaya Government OPD Budget Management - Dinda Fitriandini; Tituk Diah Widajantie (Accounting and Finance Studies, 2021)
This study aims to examine (1) the effect of budgetary participation on budget effectiveness, (2) the effect of the use of information technology on the effectiveness of budget management, (3) the effect of budget revisions on the effectiveness of budget management. The endogenous variable used is the effectiveness of budget management. This study used a sample of Surabaya City Regional Apparatus Organizations, namely 21 Surabaya City Offices. The method used to collect data was purposive sampling method, by distributing questionnaires. Data analysis techniques used Partial Least Square (PLS) with SmartPLS 3.0 software. The results of this study indicate that (1) budget participation has an effect on the effectiveness of budget management, (2) the use of information technology has no effect on the effectiveness of budget management, (3) budget revision has an effect on the effectiveness of budget management.